The Visual Impairment of Inherited Retinal Diseases in Portugal as per the National Table of Disabilities - Ana Marta, MD, MSc; Vasco Miranda, MD, MSc; Miguel Lume, MD, MSc; Ricardo Parreira, MD, MSc; Célia Azevedo Soares, MD, PhD; Maria João Menéres, MD, MSc; Carolina Lemos, PhD; João Melo Beirão, MD, PhD (Ophthalmology Science, 2024)
Purpose: To evaluate the visual impairment of patients with inherited retinal diseases (IRDs), as per the national table of disabilities (TNI). Design: Retrospective, single-center cohort study. Participants: Patients with a clinical diagnosis of IRD were recruited at a referral center in Portugal. Methods: Demographics and clinical data were collected from each individual patient file. The estimated visual disability coefficient was calculated through the evaluation of 7 graduated categories: orbital or eyelid deformities, low vision, visual field change, loss of bi-foveolar fixation, oculomotor palsy, photophobia, and chronic conjunctivitis. The TNI provides minimum and maximum disability values for numerous conditions within each category, which were summed to calculate an overall summary disability coefficient for each patient. Main Outcome Measures: Demographic/clinical and estimated minimum and maximum visual disability coefficient according to the TNI for each patient. Results: This study included 253 patients from 214 families, aged 3 to 80 years, with a mean age of 39.8 ± 20.0 years. The mean estimated minimum and maximum visual disability coefficients as per the TNI were 0.6 ± 0.4 and 0.7 ± 0.4, respectively. The low vision was the single most frequent contributor category (21.7%) present in the calculation of visual impairment. Low vision and visual field changes were the most frequent double combination (18.2%), and the addition of loss of bi-foveolar fixation was the most frequent triple combination (8.3%). Conclusions: This study found that IRD patients had a significant visual disability, with the majority having a disability coefficient ≥0.6, which would qualify them for a “multipurpose disability medical certificate.” Financial Disclosure(s): The authors have no proprietary or commercial interest in any materials discussed in this article.